On the morphological differentiation between Libinia spinosa and L. ferreirae (Crustacea: Brachyura: Majoidea: Epialtidae) - Tavares,Marcos (2012)
Libinia spinosa H. Milne Edwards in Guérin, 1832 and L. ferreirae Brito Capello, 1871, inhabit very similar environments, and their geographic and bathymetric distributions overlap for about 3000 km along the southwestern Atlantic. Both species are commonly caught in the same haul and differentiating between them can often be difficult. Traditionally, morphological differentiation between L. spinosa and L. ferreirae has been based exclusively on the number of spines along the median, longitudinal line of the carapace and the development of a process at the anterolateral angle of the basal segment of the antenna. Because Libinia spinosa and L. ferreirae share similar numbers of median spines (7 and 6, respectively), and the number of median spines of the carapace and the process at the anterolateral angle of the basal antennal segment are variable, they are of little value in separating these species. It is shown herein that unequivocal identification can be easily achieved based on features of the male and female thoracic sternum, pereiopod dactyli, and infraorbital notch. A lectotype is designated for L. spinosa and its authorship and date are corrected. Libinia gibbosa A. Milne-Edwards, 1878, is demonstrated to be a junior synonym of L. ferreirae. The holotype of L. gibbosa is figured for the first time.